The Influence Of Time Budget Pressure And Dysfunctional Behavior To Audit Quality At Bawasda In Gorontalo Province - Rio Monoarfa; Hais Dama (Jurnal Akuntansi, 2018)
Abstract: This Study is aimed to find out: (1) the influence of time budget pressure and dysfunctional behavior to audit quality simultaneously, and (2) the influence of time budget pressure and dysfunctional behavior to audit quality partially. Population in this study are all auditors of Offices of BAWASDA in Gorontalo Province. The study has used a census method, whereas its data collection techniques were done through spreading and filling questionnaires and direct interviews. Hypotheses in this study have been tested using a path analysis. The results of the study have shown that time budget pressure and dysfunctional behavior have simultaneously and partially affected the audit quality.